PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS VII2 SMPN 25 PEKANBARU - Siahaan, Refania; Maimunah, Maimunah; Jalinus, Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research to improve the learning process and the student’s mathematical understanding skill by Discovery Learning (DL) model. The type of this research is Classroom Action Research with two cycles. The subjects of this research were students of class VII2 SMPN 25 Pekanbaru. This study was conducted in the second semester of academic year 2017/2018. The research instruments used are mathematical learning instruments (Syllabus, Lesson Plans, and Student Worksheet) and instruments for collecting data (Observation Sheets and Mathematical-Understanding Tests). The observation sheets were used to find out the data of students and teacher activity during learning process which would analyzed quantitatively and qualitatively, and mathematical understanding test were used to collect the student’s mathematical understanding skill outcomes which would analyzed quantitatively. Based on the analysis of the observation sheets showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Result of the test indicates that the student’s learning achievement for the first is 48.03 improved in cycle I to 64.21 and improved to 81.37 in cycle II. The improvement of student’s learning achievement founded for each indicator of mathematical understanding skill: redefine the concept, provide examples and not examples the concept, and applying concepts to solve the problem. Based on the result above, it can be concluded that the implementation of Discovery Learning model approach can improve the learning process and the students’ mathematical understanding skill outcomes at class VII2 SMPN 25 Pekanbaru.Key Words: mathematical understanding skill, discovery learning, classroom action research